An Assessment of Digital Transformation and Maturity in the South African banking sector - Garane, Achumile Sinazo (University of the Witwatersrand, Johannesburg, 2024)
The present study investigates the nuances of digital transformation and maturity in the South African banking sector. In the present study, the prevailing problem is that documented scientific evidence seemingly suggests business customers have to wait a long time for their loan applications to be accepted because banks lack the necessary digital capabilities, business processes and IT competencies to respond to all sales requests promptly. To deal with this pressing empirical and practical gap in the literature, this study collected primary data through a semi-structured interview approach. To do this, two samples were drawn from business executives and retail and business client strata from the banking sector in South Africa. A total of 15 interviews were conducted, comprising 7 business executives and 8 from the retail and business clients group. Data was analysed using thematic analysis. The findings suggest that South Africa's banking industry has a well-advanced digital banking system that integrates business and retail clients with the global financial system and makes it easier for them to plan their cash flow streams using different products offered by digital banking platforms. Nonetheless, despite a relatively advanced banking system, evidence suggests that retail and business banking clients lack the knowledge on how to use digital banking applications. As such, the study recommends that financial institutions should develop user-friendly products, increase knowledge of product usage to clients, and eliminate the probability of cybercrime in digital banking platforms
A Dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Business Administration To The Faculty of Commerce, Law, and Management Wits Business School At The University of the Witwatersrand, Johannesburg 2024
Keywords: Digital transformation; Digital Maturity; Banking; Digital business; UCTD; SDG-8: Decent work and economic growth